In search of Filipina artists during the Japanese occupation (1942-1945) - Campos, Catherine Eloise Sarmiento
The Japanese Occupation of the Philippines represents a significant epoch in the history of our nation. Abrupt changes took place in the field of arts and culture, which prior to 1942 was enjoying the integration of Western Influences and the globalization that the American education system provided. This three-year break from the emerging modernist movement that was beginning to cement itself in the Philippine Art History saw not only the disappearance of Western Art but also of the FIlipina artists, who under the reign and propaganda of the Japanese had very limited value outside of the household. It is important to note that this dark time had not only lasting effects on the visual arts, but also on the country.